Penanaman Mangrove sebagai Revitalisasi Ekowisata Desa Kartika Jaya, Kecamatan Patebon, Kabupaten Kendal - Faizal Dicky Hermansyah; Anita Rahma Fauziah; Alya Nabila Adistia; Abdulloh Nauval Alvian Baehaqi; Zakiyah Desiana Rose; Hanik Rosyida (Lembaga Pengembangan Kinerja Dosen, 2024)
The community service program in Kartikajaya Village aims to develop local economic potential through mangrove planting as a tourist attraction. Kartikajaya Village has geographical conditions that support the development of ecotourism, but the lack of public awareness and understanding of the benefits of mangroves is a major obstacle. This activity involves local communities in the process of planting and maintaining mangroves, as well as providing education about the importance of mangroves in maintaining the balance of coastal ecosystems and increasing village tourism attractiveness. The results of this program showed an increase in community awareness of environmental conservation as well as an increase in tourist visits to the village. Thus, mangrove planting not only serves as an environmental conservation effort, but also as a driver of economic growth through the tourism sector in Kartikajaya Village.